Beneficial effects of mineralocorticoid receptor blockade in experimental non‐alcoholic steatohepatitis. (23rd February 2015) - Pizarro, Margarita; Solís, Nancy; Quintero, Pablo; Barrera, Francisco; Cabrera, Daniel; Rojas‐de Santiago, Pamela; Arab, Juan P.; Padilla, Oslando; Roa, Juan C.; Moshage, Han; Wree, Alexander; Inzaugarat, Eugenia; et al.
Abstract Background Therapeutic options to treat Non‐alcoholic steatohepatitis (NASH) are limited. Mineralocorticoid receptor (MR) activation could play a role in hepatic fibrogenesis and its modulation could be beneficial for NASH. Aim To investigate whether eplerenone, a specific MR antagonist, ameliorates liver damage in experimental NASH. Methods C57bl6 mice were fed a choline‐deficient and amino acid‐defined (CDAA) diet for 22 weeks with or without eplerenone supplementation. Serum levels of aminotransferases and aldosterone were measured and hepatic steatosis, inflammation and fibrosis scored histologically. Hepatic triglyceride content (HTC) and hepatic mRNA levels of pro‐inflammatory pro‐fibrotic, oxidative stress‐associated genes and of MR were also assessed. Results CDAA diet effectively induced fibrotic NASH, and increased the hepatic expression of pro‐inflammatory, pro‐fibrotic and oxidative stress‐associated genes. Hepatic MR mRNA levels significantly correlated with the expression of pro‐inflammatory and pro‐fibrotic genes and were significantly increased in hepatic stellate cells obtained from CDAA‐fed animals. Eplerenone administration was associated to a reduction in histological steatosis and attenuation of liver fibrosis development, which was associated to a significant decrease in the expression of collagen‐α1, collagen type III, alpha 1 and Matrix metalloproteinase‐2. Conclusion The expression of MR correlates with inflammation and fibrosis development in experimental NASH. Specific MR blockade with eplerenone has hepatic anti‐steatotic and anti‐fibrotic effects. These data identify eplerenone as a potential novel therapy for NASH. Considering its safety and FDA‐approved status, human studies are warranted.